High emission of carbon dioxide and methane during ice thaw in high latitude lakes. Issue 6 (16th March 2013) - Karlsson, Jan; Giesler, Reiner; Persson, Jenny; Lundin, Erik
Abstract : [1] The winter period is seldom included in the estimates of aquatic‐atmospheric carbon exchange. In this study we quantified the flux of carbon dioxide (CO2 ) and methane (CH4 ) over 3 years from 12 small subarctic lakes. The lakes accumulated consistent and high amounts of CO2 and CH4 (56–97% as CO2 ) over the winter, resulting in a high flux during ice thaw. The CO2 flux during ice thaw increased with increasing mean depth of the lakes, while the CH4 flux was high in lakes surrounded by mires. The ice thaw period was quantitatively important to the annual gas balances of the lakes. For nine of the lakes, 11 to 55% of the annual flux occurred during thaw. For three of the lakes with an apparent net annual CO2 uptake, including the thaw period reversed the balance from sink to source. Our results suggest that the ice thaw period is critically important for the emissions of CO2 and CH4 in small lakes. Key Points: High winter accumulation and spring flux of CO2 and CH4 from the lakes Carbon flux at ice‐thaw was related to lake depth and catchment characteristics The flux at ice‐thaw was important for annual carbon exchange with atmosphere